Challenges and applications of data analytics in social perspectives - Sathiyamoorthi, V., 1983-; Elçi, Atilla (Advances in data mining and database management (ADMDM) book series., 2021)
""This book focuses on prevailing challenges in data analytics and its application on social media like Facebook, Twitter, blogs, e-commerce, and e-service"--Provided by publisher"--